Revisión bibliográfica sobre el síndrome abdominal agudo en equinos 2022 (2022)
This research was born from the need to synthesize the existing information on Acute Abdominal Syndrome (SAA) in equines, this being the main cause of death in this type of animals in cases where it is not diagnosed in a timely manner, so analyze the state of the art (SAA), its causes, predisposing factors, signs, diagnostic methods and available treatments, would contribute to a better understanding and management of said condition by the professionals involved in the care of these animals . Through the bibliographic review carried out in various specialized and non-specialized databases, studies have been compiled that deal with the subject from different perspectives, yielding as a result ...